Community empowerment in creative healthy food entrepreneurship as strengthening the community economy in Tutul Village - Diyan Indriyani; Asmuji Asmuji; Triawan Adi Cahyanto; Astrid Maharani; Sri Wahyuni Adriani (Universitas Muhammadiyah Magelang, 2022)
By developing the community's capacity for entrepreneurship, one of which is in the food business, one can empower the community economically. Tutul Village is a productive village with entrepreneurship activities centered on handicrafts, but there aren't any yet in food sector, especially creative healthy food. The team carried out in activities to improve entrepreneurship skills throughout the third year of the Partner Village Development Program, particularly creative healthy food products for pregnant women, nursing mothers, infants, toddlers, school-age children, the elderly, and people with chronic diseases. The training participants were 12 prospective entrepreneurs from 4 hamlets in Tutul Village. The five stages of the training were completed with assistance. Assistance in the form of competency improvement, labeling and packaging, assessment of nutritional content, production permits, and marketing. There are 11 healthy food products with creative presentations that are stimulants for prospective entrepreneurs to develop. Prospective entrepreneurs should be highly motivated to launch new food products so that the marketing of creative healthy food products can be easily recognized by the the general public.